The Cultural Geography on the III Millennium: epistemic-methodological and educational perspectives - Marcos Antonio Correia (Universidade Estadual Paulista Júlio de Mesquita Filho, 2010)
The article puts in evidence the Cultural and Humanistic Geography and its new shapes of working with the knowledge. For such thing, it reflects about the geographic knowledge on the third millennium and the new humanistic perspectives of this lore. So that it points out the feeling and the emotion starting from the subjectivism and from the relation people have with their own living and realized space. These reflections are treated as a general and a geographical knowledge, but more particularly in a geographical sight, pointing out in this last, the categories which envolve the daily life of the local citizens, the more evident and substantials to the grasp in the positioned geographical science, as well, for the teaching of this subject. Reflects also about the position of the contemporary knowledge, as well as pointing out the possible contribution Geography may bring to the efectiveness of those. For that reason, it points some metodologic and pedagogical questions of the actual geography, reaching fenomenological grounds of the social representations, for the elaboration of one more human lore, particularly inside the geographical science, which could contribute to the project of the society at all. For this, the fenomenological vision of Husserl and Merleau-Ponty it is put in evidence, like the Moscovici's theory of social plays. These theories go towards one humanistic geography to be built and reflected in an academic, educational and pedagogical environment.